Phytochemical screening and antibacterial activities of Dioscorea hispida (Dennst.) against wound pathogen / Mohammad Azri Azmi - Azmi, Mohammad Azri (2014)
Dioscorea hispida (Dennst.) tuber is a species of edible yam. It needs special preparation technique for the yam to be safely consumed. The yam bulb paste is used to treat minor wound by people of Satpuda Hill, India. In this study, the phytochemical screening of the D. hispida before and after treatment was carried out to determine the phytochemical compound and the impact of treatment toward the phytochemical compound. This study also was aimed to determine the antibacterial activities of the treated and untreated D. hispida tuber extract against wound pathogen, namely Serratia marcescens (ATCC 14756) and Pseudomonas aeruginosa (ATCC 10145). The treatment is carried out by rinsing the tuber cutlets in running water for 7 days in accordance to the traditional method. This study discover that the tuber of D. hispida contains carbohydrate, alkaloid, phenols, steroid, tannins and terpenoids. The treatment process was found to eliminate the content of alkaloid, phenols, tannins and terpenoid. From the disc diffusion test on the treated and untreated D. hispida tuber extract, it is found that the tuber is ineffective in inhibiting growth of wound pathogen, the S. marcescens and P. aeruginosa.